2016
DOI: 10.1007/s40519-016-0312-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: not just the bone. Evidence for beneficial pleiotropic extraskeletal effects

Abstract: Vitamin D is a fat-soluble vitamin and a steroid hormone that plays a central role in maintaining calcium-phosphorus and bone homeostasis in close interaction with parathyroid hormone, acting on its classical target tissues, namely, bone, kidney, intestine, and parathyroid glands. However, vitamin D endocrine system regulates several genes (about 3 % of the human genome) involved in cell differentiation, cell-cycle control, and cell function and exerts noncalcemic/pleiotropic effects on extraskeletal target ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 130 publications
1
78
0
12
Order By: Relevance
“…Obesity has a negative correlation with plasma vitamin D levels, and vitamin D deficiency causes an increased risk for the development of metabolic syndrome, as well as increased oxidative burden. 4 …”
Section: Uv-b Raysmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity has a negative correlation with plasma vitamin D levels, and vitamin D deficiency causes an increased risk for the development of metabolic syndrome, as well as increased oxidative burden. 4 …”
Section: Uv-b Raysmentioning
confidence: 99%
“…Today, this substance is called vitamin D. 4 Physical activity has always existed throughout history, both indoors ( Figure 1) and outdoors 5 ( Figure 2). Millennial accounts of Greeks, Chinese and Indians in relation to the practice of physical activity affirm the idea that a stimulated body becomes strong regardless of variation in the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated the role of vitamin D in obesity through different genetic, experimental, epidemiological and metabolic data linking adipokines with Vitamin D [2][3][4][5]. Vitamin D produces its effects through its binding to vitamin D receptor (VDR); a nuclear transcription factor [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in animals, perception of the hormone acetylcholine triggers contraction in striated muscles, reduces contractions in heart muscle and promotes secretion of digestive enzymes in pancreatic acinar cells 265 ; the hormone progesterone is involved in control of reproduction and sexual behavior but also has effects in the nervous system where it is involved in adult neurogenesis, astroglial and synaptic plasticity, and the myelination process 266 ; vitamin D is involved in calcium-phosphorus maintenance and bone homeostasis, cell differentiation, cell-cycle control, glucose metabolism, muscle and adipose tissue function 267 . This variety of responses is seen also for plant hormones, like auxin.…”
Section: Discussionmentioning
confidence: 99%